Étude des critères de fiabilité des bancs miniers : le cas de la fosse Tiriganiaq au Nunavut - Grenon, Martin; Kabuya Mukendi, Joseph; Hadjigeorgiou, John; Matte, Pierre; Brunet, Francis; LeBlanc, Daniel B. (Canadian Institute of Mining Metallurgy and Petroleum, 2012)
Bench stability in mines is an important element of pit design. There is no consensus on which criteria to use to evaluate the bench design reliability. When designing the pits, bench design reliability is analyzed according to one or two criteria. The objective of this paper is to analyze the bench design for the Tiriganiaq pit, part of the Meliadine mine project, with regards to the reliability criteria found in the literature and in practice. The paper presents the similarities and the differences between the results obtained according to the various criteria and it proposes a systematic multicriteria approach to evaluate pit bench design reliability using susceptibility maps.